A new low molecular weight, MnII-containing scavenger of superoxide anion protects cardiac muscle cells from hypoxia/reoxygenation injury. (January 2015) - Nistri, S.; Boccalini, G.; Bencini, A.; Becatti, M.; Valtancoli, B.; Conti, L.; Lucarini, L.; Bani, D.
Abstract Reperfusion injury after oxygen starvation is a key pathogenic step in ischemic diseases. It mainly consists in oxidative stress, related to mitochondrial derangement and enhanced generation of reactive oxygen species (ROS), mainly superoxide anion (O22), and peroxynitrite by cells exposed to hypoxia. This in vitro study evaluates whether MnII(4, 10-dimethyl-1, 4, 7, 10-tetraazacyclododecane-1, 7-diacetate).2H2O, or MnII(Me2DO2A), a new low molecular weight, MnII-containing O2 scavenger, has a direct protective action on H9c2 rat cardiac muscle cells subjected to hypoxia and reoxygenation. MnII(Me2DO2A) (1 and 10 μmol/l) was added to the culture medium at reoxygenation and maintained for 2 h. In parallel experiments, the inactive congener ZnII(Me2DO2A), in which ZnII replaced the functional MnII center in the same organic scaffold, was used as negative control. MnII(Me2DO2A) (10 μmol/l) significantly increased cardiac muscle cell viability (trypan blue assay), improved mitochondrial activity (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide test, membrane potential Δψ), reduced apoptosis (mitochondrial permeability transition pore opening, caspase-3, terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling assay), decreased intracellular ROS levels (2', 7'-dichlorodihydrofluorescein diacetate and MitoSOX assays), and decreased protein nitroxidation (nitrotyrosine [NT] expression) and DNA oxidation (8-hydroxy-deoxyguanosine levels). Of note, ZnII(Me2DO2A) had no protective effect. The mechanism of MnII(Me2DO2A) relies on concentration-dependent removal of harmful O2 generated at reoxygenation from dysfunctional mitochondria in hypoxia-induced cells, as indicated by the MitoSOX assay. This study suggests that MnII(Me2DO2A) is a promising antioxidant drug capable of reducing O2-mediated cell oxidative stress which occurs at reoxygenation after hypoxia. In perspective, MnII(Me2DO2A) might be used to reduce ischemia–reperfusion organ damage in acute vascular diseases, as well as to extend the viability of explanted organs before transplantation.